THE REPRESENTATION OF FEMALE CHARACTER IN EDGE OF TOMORROW (2014) FILM BASED ON FEMINIST FILM CRITICS - Prismanisa, Lana (Diksi, 2021)
(Title: The Representation of Female Character in "Edge of Tomorrow" (2014) Film Based on Feminist Film Critics). This research analyzes the female character in Edge of Tomorrow, Rita Vrataski. This research intends to understand how female character is described in the film and how female character is described according to feminist film critic. The method used is descriptive qualitative method. This research also uses theory character and characterization in film and theory feminist film critic. As the result, Rita is described as a female soldier who has characteristics as committed, brave, assertive, strong, muscular, intelligent and skillful soldier. Even though Rita, as the female character who has man's characteristics, she still needs help from another male character. Rita character in this film is still passive because the one who finishes the mission in the story is the male character, William Cage. This film proves that male domination still exists in story of film. Thus, the female stereotype has been attached in film and it is difficult to change it.Keywords: female character ,women in film , feminist film critic